Proton pump inhibitors may enhance the risk of digestive diseases by regulating intestinal microbiota - Tian, Liang; Huang, Chongfei; Fu, Wenkang; Gao, Long; Mi, Ningning; Bai, Mingzhen; Ma, Haidong; Zhang, Chao; Lu, Yawen; Zhao, Jinyu; Zhang, Xianzhuo; Jiang, Ningzu; et al. (Frontiers in Pharmacology, 2023)
Proton pump inhibitors (PPIs) are the most used acid-inhibitory drugs, with a wide range of applications in the treatment of various digestive diseases. However, recently, there has been a growing number of digestive complications linked to PPIs, and several studies have indicated that the intestinal flora play an important role in these complications. Therefore, developing a greater understanding of the role of the gut microbiota in PPI-related digestive diseases is essential. Here, we summarize the current research on the correlation between PPI-related digestive disorders and intestinal flora and establish the altered strains and possible pathogenic mechanisms of the different diseases. We aimed to provide a theoretical basis and reference for the future treatment and prevention of PPI-related digestive complications based on the regulation of the intestinal microbiota.